2014
DOI: 10.1578/am.40.1.2014.44
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sex, Seasonal Period, and Sea State on Calf Behavior in Hawaiian Humpback Whales (Megaptera novaeangliae)

Abstract: Ontogeny of behavior in young humpback whale (Megaptera novaeangliae) calves likely reflects preparation for adulthood, including courtship and reproductive activities, predator avoidance, and prey capture. Reproductive strategies differ for males and females, with males competing aggressively for females, while females focus their energy on raising calves; thus, certain behaviors may develop differently in each sex. In addition to these forces driving behavioral development, ambient conditions, such as Beaufo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…Thus, low level vocalisations may serve to keep contact without attracting unwanted attention, at the expense of a very small communication range between mother-calf pairs meaning that mothers and calves must keep close. Supporting this, we and others have observed that humpback whale calves rarely separate from their mother by more than a few tens of metres (Glockner & Venus 1983;Zoidis et al 2014). Other humpback whale calls are produced at levels appropriate to the intended audience: a long communication range is favoured for songs to reach a large audience while the quieter social sounds are intended for the immediate group (Dunlop et al 2013).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Thus, low level vocalisations may serve to keep contact without attracting unwanted attention, at the expense of a very small communication range between mother-calf pairs meaning that mothers and calves must keep close. Supporting this, we and others have observed that humpback whale calves rarely separate from their mother by more than a few tens of metres (Glockner & Venus 1983;Zoidis et al 2014). Other humpback whale calls are produced at levels appropriate to the intended audience: a long communication range is favoured for songs to reach a large audience while the quieter social sounds are intended for the immediate group (Dunlop et al 2013).…”
Section: Discussionsupporting
confidence: 56%
“…Supporting this, we and others have observed that humpback whale calves rarely separate from their mother by more than a few tens of metres (Glockner & Venus ; Zoidis et al . ). Other humpback whale calls are produced at levels appropriate to the intended audience: a long communication range is favoured for songs to reach a large audience while the quieter social sounds are intended for the immediate group (Dunlop et al .…”
Section: Discussionmentioning
confidence: 97%
“…Hydrophones systems were a combination of a single omnidirectional hydrophone (Cetacean Research Technology SQ26-06 hydrophone custom mounted and cabled to 1 m below the camera) and a custom designed (Adam Frankel, Cornell Lab of Bioacoustics) two-element hydrophone array with two HTI MIN-96 hydrophones mounted 1.5 m apart on a bar perpendicular to the optical axis of the camera. Standardized methods for in-water sampling were followed from previously published humpback whale studies [ 5 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Surface observation notes were taken of all surface and underwater focal bouts and photographs were taken with a Canon 10D digital camera and 300 mm lens by 1–2 vessel-based observers. Focal sessions focused primarily on any groups with a mother and calf to assess under- and above-water behaviors, group associations, laterality, and underwater vocalizations using sampling methods described in detail in Zoidis et al, 2008 [ 26 ] and Zoidis et al, 2014 [ 27 ]. Prior to initiating a focal session, baseline observations were made to examine if behavioral states differed before and after free-divers entered the water.…”
Section: Methodsmentioning
confidence: 99%
“…An ethogram was constructed to represent the complete activity budget of mother-calf pairs and behavioral states were considered mutually exclusive to one another ( Table 1). The five behavioral states used are similar to those used for a previous study on the behavior of NARW mother-calf pairs (Hain et al, 2013), as well as for other cetaceans including grey whales Eschrichtius robustus (Stelle, Megill & Kinzel, 2008), southern right whales Eubalaena australis (Taber & Thomas, 1982;Thomas & Taber, 1984), humpback whales (Cartwright & Sullivan, 2009;Zoidis et al, 2014), and killer whales Orcinus orca (Ford, 1989). The duration of time spent in these key behavioral states was calculated for each focal follow to determine the overall activity budget.…”
Section: Behavioral Data Collectionmentioning
confidence: 99%